2008
DOI: 10.1158/1078-0432.ccr-08-1064
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of HER3 Is Associated with a Decreased Survival in Gastric Cancer

Abstract: Background: The role of human epidermal growth factor receptor (HER) 3 and HER4 has been elucidated in gastric cancer. HER1 and HER2 overexpression are regarded as prognostic factors and targets of treatment. The dimerization of the HER family receptors activates downstream signal pathways and promotes tumor progression. This study investigated the positive correlation between HER1and HER4 expression and the prognosis of patients with gastric cancers. Experimental Design: Tumor samples were obtained from gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 53 publications
12
102
3
2
Order By: Relevance
“…We demonstrated that the co-expression of HER3 and HER4 at 35% was statistically significant (P=0.019), suggesting that again, HER3 may be acting as a preferred dimerization partner for EGFR family A B members. Indeed, Hayashi and colleagues demonstrated that HER3 membranous expression was also significantly correlated with HER4 expression and associated with tumor progression, higher depth of tumor invasion (T1 vs. T2-T4) involved lymph nodes, distant metastasis tumor stage, recurrences and worse survival (37). We noted overexpression of all EGFR family members in only 17% of the cases.…”
Section: Discussionmentioning
confidence: 49%
“…We demonstrated that the co-expression of HER3 and HER4 at 35% was statistically significant (P=0.019), suggesting that again, HER3 may be acting as a preferred dimerization partner for EGFR family A B members. Indeed, Hayashi and colleagues demonstrated that HER3 membranous expression was also significantly correlated with HER4 expression and associated with tumor progression, higher depth of tumor invasion (T1 vs. T2-T4) involved lymph nodes, distant metastasis tumor stage, recurrences and worse survival (37). We noted overexpression of all EGFR family members in only 17% of the cases.…”
Section: Discussionmentioning
confidence: 49%
“…Early Grabsch et al, 11 Marx et al, 15 Yu et al, 19 Hayashi et al, 22 Potrc et al, 23 Song et al, 30 Pinto-de-Sousa et al, 34 Ghaderi et al 36 [15 Studies (7 studies between 1990 and 1999 not displayed)]…”
Section: /4mentioning
confidence: 99%
“…Not specified Wang et al, 10 Im et al 27 [2 Studies] Marx et al, 15 Yu et al, 19 Hayashi et al, 22 Satiroglu-Tufan et al, 25 Ghaderi et al, 36 Allgayer et al 39 15 Barros-Silva et al, 16 Hayashi et al, 22 Park et al, 24 Tanner et al, 26 Song et al, 30 Garcia et al, 31 Lee et al, 32 Pintode-Sousa et al, 34 Oshima et al 38 [12 Studies (2 studies between 1990 and 1999 not displayed)]…”
Section: Presence Of Metastases (M)mentioning
confidence: 99%
“…Intestinal type has predominance of HER2 overexpression over HER3, while diffuse type has increased overexpression of HER3 compared to HER2 [23]. In a study where gastrectomy samples were obtained from 134 patients with gastric adenocarcinomas, HER3 overexpression was significantly correlated with increased depth of tumor invasion, involved lymph nodes, distant metastasis, more advanced tumor stage, and increase in recurrent disease [24]. HER3 overexpression served as a poor prognostic factor in this study.…”
Section: Her Family Receptors and Gastric Cancermentioning
confidence: 60%